Evaluation of seed-borne fungi associated with tomato and their control measures (Jahangirnagar University Journal of Biological Sciences, 2018)
A number of seed borne fungi such as- Fusarium moniliforme, Curvularia lunata, Alternaria solani, Helminthosporium solani, Aspergillus flavus, A. niger and Penicillium spp. were identified from the selected BARI-8, Nilima, Patharkuchi, Roma and Ratan varieties of tomato seeds. The highest (2.53%) mean incidence of the fungi F. moniliforme were recorded in tomato variety Roma, BARI-8, Nilima and Ratan while the lowest (0.13%) mean incidence of the fungi Penicillium was found in Ratan. The maximum percent of germination (64%) was recorded in both BARI-8 and Patharkuchi varieties, while the minimum (7%) germination in Nilima. The highest seedling vigor index (632.96) was encountered in BARI-8 and the lowest in Nilima. Trichoderma viride, T. harzianum and T. koningii were used as bio-control agents against major seed borne fungi. T. viride showed the significantly effective mycelial growth inhibition against F. moniliforme and C. lunata, while T. harzianum and T. koningii showed poor performance against both tested fungi. In case of botanical extracts, Lawsonia inermis exhibited the maximum (82.15% and 86.24%) inhibition of mycelium growth of F. moniliforme and C. lunata, respectively. Chemical fungicides, Bavistin (0.5 gm/l) inhibited 65% mycelial growth against F. moniliforme, while higher concentration of chemical fungicide gave 81% inhibition of C. lunata. The results suggested that, L. inermis phytoextract can possibly be exploited for the management of seed-borne pathogenic fungi of tomato in an environmental friendly way.Jahangirnagar University J. Biol. Sci. 6(2): 59-66, 2017 (December)